RANCANG BANGUN HETEROGENOUS DISTRIBUTED DATABASE SYSTEM UNTUK MENINGKATKAN KAPASITAS ORACLE XE 10G PADA STUDI KASUS SISTEM INFORMASI AKADEMIK - Muhammad Didik Rohmad Wahyudi; Anas Azhimi Qalban (Kaunia: Integration and Interconnection Islam and Science, 2013)
Oracle XE 10g (Express Edition) is an Oracle edition which purposed to the requirement of the data management for small enterprise to the middle enterprise which freeware licence. Unfortunately, Oracle XE 10g database capacity limited 4 GB. One of the methods in a distributed database system is heterogenous distributed database systems use partialy connected network topology to solve the problem of the capacity limit at Oracle XE 10g. To increase the data storage capacity, the oracle XE database connected to the MySQL database with the help of the simulation database ODBC link academic information system.